The potential protective effect of metformin on selective cardiac biomarkers in diabetic male rats - Yahya G. Karwi; Inam S. Arif; Muthanna I. Al-Ezzi (College of Pharmacy / Mustansiriyah University, 2018)
Metformin, a biguanide, first line antidiabetic agent, undergoes extensive debate to explain its possible cardioprotective effect. This study represents an attempt to help clarifying this cardioprotective effect. 24rats divided into three diabetic group (8 rats for each) (diabetes induced by Streptozocin 60 mg/kgi.p.). Diabetic groups treated with (saline, 75 mg/kg metformin and 150 mg/kg metformin, i.p.) for 6 weeks, then cardiac stress was induced by isoproterenol (ISO) (150 mg/kg i.p.) for two successive days. Selective biomarkers were assessed; brain natriuretic peptide (BNP), matrix metalloproteinase - 1 (MMP-1) and histopathology examination. The results of this study showed that metformin produce a dose dependent cardioprotection effect in diabetic rats.